Melaksanakan Amanat Agung Tuhan Yesus Melalui Pola Pelayanan yang Utuh - Adrianus Pasasa (STT INTI Bandung, 2024)
The Great Commission is a command given by the Lord Jesus to His disciples before being ascended to Heaven. This command remains in effect and must be carried out until the end of time. This command is the core of God's mission to save humanity who has fallen into sin by reconciling humans to Himself, through the sacrifice of His son on the cross. The scope of the great commission is that every tribe, language, nation and people on the face of the earth can hear the message of the Gospel. Therefore, the church must be the main agent in carrying out the great commission. The church must carry out the great commission as a whole, where the church must be involved in being part of sending mission personnel to the mission field. The church must be part of equipping personnel who are ready to go preach the Gospel and the church must take part in discipling people who have heard and accepted the Gospel. The Lord Jesus has provided a real example through his ministry while in this world, where He carried out a complete service, namely sending His disciples to go preach the gospel, preparing Himself as a source of teaching and also training His disciples to give birth to new disciples.